PERNERAPAN MODEL PERSAMAAN SIMULTAN DENGAN PENDEKATAN TWO STAGE LEAST SQUARE PADA KASUS INFLASI DAN NILAI TUKAR RUPIAH DI INDONESIA - Rahmawati Yusuf; Resmawan Resmawan; Boby Rantow Payu (Universitas Negeri Gorontalo, 2021)
Using the regression model, a method that accommodates variables related to each other is called the simultaneous equation method. The study aims to determine the factors affecting inflation and rupiah exchange rate and model simultaneous equations towards the factors affecting inflation and rupiah exchange rate in Indonesia using Two-Stage Least Square. Data used in this study are secondary data obtained from the website of Statistics of Indonesia. Findings on the simultaneous equation model with two-stage least squares reveal that variables that significantly affect inflation are the Indonesia rupiah exchange rate and money supply. At the same time, variables that significantly affect the Indonesian rupiah exchange rate are inflation and money supply. The predictive value using the inflation and rupiah exchange rate equation indicates that the obtained MAPE (Mean Absolute Percentage Error) value does not exceed 50%. In conclusion, the prediction result using the inflation and Indonesia rupiah exchange rate equation is accurate.